Design, Construction, and Validation of an Internally Lit Air-Lift Photobioreactor for Growing Algae - Hincapie, Esteban; Stuart, Ben J. (Frontiers in Energy Research, 2015)
A novel 28 L photobioreactor for growing algae was developed using fiber optics for internal illumination. The proposed design uses the air-lift principle to enhance the culture circulation and induce light/dark cycles to the microorganisms. Optical fibers were used to distribute photons inside the culture media providing an opportunity to control both light cycle and intensity. The fibers were coupled to an artificial light source; however, the development of this approach aims for the future use of natural light collected through parabolic solar collectors. This idea could also allow the use of opaque materials for photobioreactor construction significantly reducing costs and increasing durability. Internal light levels were determined in dry conditions and were maintained above 80 μmol/(s·m2). The hydrodynamic equations of the air-lift phenomena were explored and used to define the geometric characteristics of the unit. The reactor was inoculated with the algae strain Chlorella sp. and sparged with air. The reactor was operated under batch mode and daily monitored for biomass concentration. The specific growth rate constant of the novel device was determined to be 0.011 h−1. The proposed design can be effectively and economically used in carbon dioxide mitigation technologies and in the production of algal biomass for biofuel and other bioproducts.